(untitled) (INNOVATIVE ECONOMY, 2026)
Balaniuk I.F., Melnyk I.O. REGULATORY AND LEGAL FRAMEWORK FOR THE FORMATION OF ACCOUNTING AND ANALYTICAL INFORMATION IN MODERN BUSINESS ENVIRONMENTS Purpose. The aim of the article is a comprehensive substantiation of the theoretical foundations of legal support and a critical analysis of the current state of regulatory and legal framework of accounting and analytical information, as well as the identification of strategic directions for harmonizing the current legislation of Ukraine with the actual needs of management in the context of the digitalization of the economy. Methodology of research. The research methodology is based on general scientific methods, which ensured a high degree of validity for the author’s conclusions. The application of epistemological analysis facilitated a thorough study of the evolutionary changes in the concept of “information”. A systems approach enabled the identification of accounting and analytical information as a complex, multifaceted entity where legal, economic, and purely technological elements intertwine. Through the comparative legal method, an analysis of the compliance of Ukrainian legislation with international standards has been conducted, while an empirical approach allowed for the investigation of practical aspects of applying legal norms within an informational context. The graphical method made it possible to visually represent the hierarchy of the transformation of accounting and analytical information. Findings. Based on the research findings, a four-level model of the regulatory framework for accounting and analytical information has been structured, ranging from the general legal (constitutional) level to the local level (accounting policy level). It was established that the classical legislative interpretation of information as “documented data” is somewhat outdated and requires modernization in light of modern cybernetic concepts and knowledge theory. The necessity of expanding legal regulation from statics (simple recording) to dynamics (processes of transforming primary data arrays into an analytical resource for top management) has been proven. The study substantiates the claim that accounting and analytical information should serve as an object of enhanced legal protection within the economic security mechanism. The critical need for a legislative distinction between the categories of “data”, “information” and “knowledge” is emphasized to eliminate legal conflicts during the implementation of control functions. Originality. For the first time, the necessity of adopting an anthropocentric model for the legal regulation of accounting and analytical information (AAI) has been substantiated. In contrast to the existing technocentric approach, this model allows for treating information not as a static record but as a dynamic intellectual asset (knowledge) with high added value. The hierarchical structure of the regulatory framework for generating accounting data has been improved. This enhancement facilitates the minimization of conflicts between transparency requirements and the protection of commercial secrets. The conceptual understanding of the local regulatory level (accounting policy) has been further developed as a “methodological bridge”. This approach ensures the legitimization of artificial intelligence outputs and cloud service results within the corporate reporting system. Practical value. The study finds that Ukraine’s current regulatory and legal framework, despite its fundamental nature, serves as an insufficient toolkit for the full-scale management of accounting systems in the era of digital challenges. The research substantiates the need for further legislative recognition of digital assets and integrated reporting as legitimate legal entities. Corresponding adaptation of legal regulations will enable a qualitative shift in the status of accounting information, transforming it from an attribute of formal reporting into powerful intellectual capital. The generalizations hold both theoretical value for academic discussion and practical significance for improving the internal regulations of business entities. Key words: accounting and analytical information, regulatory and legal framework, business, accounting policy, economic security, digitalization.